PENERAPAN ACTIVITY BASED COSTING PERHITUNGAN HARGA POKOK UNTUK MEMBANTU PENENTUAN HARGA JUAL - Nurfadhilah, Siti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Qualitative method is applied in this research, while the descriptive analysis with qualitative approachis used as the data analysis technique since it gives explanation by comparing the data which isobtained from the research to the existing theories. This research is meant to find out theimplementation product cost price by applying Activity Based Costing method and then it can be usedby the management of CV Supra Sejahtera as an alternative to determine of the establishment ofproduct cost price.The researcher recommends that the CV Supra Sejahtera should apply the calculation of productioncost price with the Activity Based Costing method since it gives accurate information about theproduction cost in accord with the determination of product cost price which can be used as afoundation in determining the product cost price.Keywords: Activity Based Costing System, Cost Plus Pricing and Determining Selling Price.